PROYEKSI POLA PERGERAKAN PADA SIMPANG BERSINYAL (MAKASSAR - SELAWESI SELATAN) - Indriaty Wulansari Indri (DAS Institute, 2022)
MAT (Origin Destination Matrix) is a two-dimensional matrix that contains information about the magnitude of movement between locations (zones) within a specific area. If a MAT is charged to a transportation network system, it will produce a movement flow that describes the movement pattern in the area. This research is quantitative descriptive research. The purpose of this research is to project the future traffic movement pattern. Four methods have been developed to date that generally tries to overcome the shortcomings of the previous method, namely the Analog method (average, Detroit, Fratar, and Furness). These four methods guarantee that the magnitude of the pull generation in the future is the same as expected. Data collection techniques in research are in the form of direct data collection in the field using video cameras placed at several observation points. Hourly flow patterns calculate traffic volume. Based on the results of the analysis, it was found that there were differences in repetition in each analog method. The average method reached the 75th repetition, the Detroit method reached the 8th repetition, the Fratar method reached the 41st repetition, and the Furness method reached the third repetition.